Timed Chi: Modeling, Simulation and Verification of Hardware Systems - Man, Ka Lok (Computing and Informatics, 2012)
Timed Chi (chi) is a timed process algebra, designed for Modeling, simulation, verification and real-time control. Its application domain consists of large and complex manufacturing systems. The straightforward syntax and semantics are also highly suited to architects, engineers and researchers from the hardware design community. There are many different tools for timed Chi that support the analysis and manipulation of timed Chi specifications; and such tools are the results of software engineering research with a very strong foundation in formal theories/methods. Since timed Chi is a well-developed algebraic theory from the field of process algebras with timing, we have the idea that timed Chi is also well-suited for addressing various aspects of hardware systems (discrete-time systems by nature). To show that timed Chi is useful for the formal specification and analysis of hardware systems, we illustrate the use of timed Chi with several benchmark examples of hardware systems.